Transformational Leadership and Employee Motivation: Inquiry into Behavioral Mechanisms within Private Enterprises. - Mukhlis Rahmatullah (HARAMAIN: Jurnal Manajemen Bisnis, 2025)
Employee motivation remains a critical issue in private enterprises because it directly affects productivity, organizational commitment, and long-term business sustainability. Among the leadership approaches widely associated with enhanced employee outcomes, transformational leadership has received substantial scholarly attention. However, limited research has examined the behavioral mechanisms through which transformational leadership influences employee motivation, particularly in the context of private enterprises in regional settings. This study aims to explore how transformational leadership shapes employee motivation through behavioral mechanisms within PT. Tamarin Jaya Lombok Timur. A qualitative case study approach was employed to obtain an in-depth understanding of leadership practices and employees’ motivational experiences in their natural organizational context. Data were collected through in-depth interviews, direct observation, and document analysis, and were analyzed using the interactive model of data condensation, data display, and conclusion drawing/verification. The findings reveal that transformational leadership influences employee motivation primarily through relational and behavioral processes, especially role modeling, consistency between words and actions, fairness, and direct leader involvement in work activities. Employees were more motivated when they perceived their leaders as trustworthy, disciplined, and worthy of emulation. The study further shows that motivation is not merely a result of formal authority or material incentives, but is constructed through employees’ interpretations of leaders’ everyday behaviors. These findings contribute to the transformational leadership literature by clarifying the micro-level behavioral mechanisms that connect leadership practices with employee motivation in private enterprise settings. Practically, the study suggests that organizations should strengthen leadership development by emphasizing integrity, relational competence, and exemplary conduct in order to foster a more motivating work environment.